Evidence of Early Diabetic Nephropathy in Pediatric Type 1 Diabetes - Mamilly, Leena; Mastrandrea, Lucy D.; Mosquera Vasquez, Claudia; Klamer, Brett; Kallash, Mahmoud; Aldughiem, Ahmad (Frontiers in Endocrinology, 2021)
Background: Diabetic nephropathy (DN) is one of the most common microvascular complications in type 1 diabetes Miletus (T1D). Urinary markers of renal damage or oxidative stress may signal early stages of DN. The association of these markers with blood pressure (BP) patterns and glycemic variability (GV) in children is yet to be explored. Methods: Subjects between the ages of 10 and 21 years with T1D were enrolled. Continuous glucose monitoring (CGM) and ambulatory blood pressure monitoring (ABPM) were performed on each subject. Urine samples were collected and analyzed for albumin, creatinine, neutrophil gelatinase-associated lipocalin (NGAL) and pentosidine. Results: The study included 21 subjects (62% female) with median age of 16.8 (IQR: 14.5, 18.9). Median HbA1C was 8.4 (IQR: 7.5, 9.3). While microalbuminuria was negative in all but one participant (4.8%), urinary NGAL/Cr and pentosidine/Cr ratios were significantly elevated (P<0.001) in diabetic patients despite having normal microalbuminuria, and they correlated significantly with level of microalbumin/Cr (r=0.56 [CI: 0.17, 0.8] and r=0.79 [CI: 0.54, 0.91], respectively). Using ABPM, none had hypertension, however, poor nocturnal systolic BP dipping was found in 48% of participants (95% CI: 28-68%). Urinary NGAL/Cr negatively correlated with nocturnal SBP dipping (r=-0.47, CI: -0.76, -0.03). Urine NGAL/Cr also showed a significant negative correlation with HbA1c measurements, mean blood glucose, and high blood glucose index (r=-0.51 [CI: -0.78, -0.09], r=-0.45 [CI: -0.74, -0.03], and r=-0.51 [CI: -0.77, -0.1], respectively). Median urinary NGAL/Cr and pentosidine/Cr ratios were higher in the high GV group but were not significantly different. Discussion: This pilot study explores the role of ABPM and urinary markers of tubular health and oxidative stress in early detection of diabetic nephropathy. GV may play a role in the process of this diabetic complication.